2009
DOI: 10.1111/j.1095-8339.2008.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among genotypes ofEryngium viviparum(Apiaceae): a plant threatened throughout its natural range

Abstract: Eryngium viviparum (Apiaceae) is an endangered aquatic plant, listed as threatened in several European documents. The genotypes are distributed patchily in various wetlands in the north-west of Spain and one is located in north-west France. The study of the genetic diversity of a small population of a rare species is important for conservation and studies aimed at recovery programmes. Random amplified polymorphic DNA (RAPD) markers were used to assess the genetic diversity among five Spanish and one French gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Coult. & Rose) Mathias & Constance, E. constancei Sheikh, E. cuneifolium Small, E. viviparum [4][5][6][7]. Wolff's (1913) treatment of Eryngium is the most comprehensive and predominant: two groups were recognized within the genus Eryngium: "Species gerontogeae" representing 12 sections from the Old World (Africa, Europe, and Asia) and "Species americanae and australienses" including 22 sections from the New World (Americas and Australia) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Coult. & Rose) Mathias & Constance, E. constancei Sheikh, E. cuneifolium Small, E. viviparum [4][5][6][7]. Wolff's (1913) treatment of Eryngium is the most comprehensive and predominant: two groups were recognized within the genus Eryngium: "Species gerontogeae" representing 12 sections from the Old World (Africa, Europe, and Asia) and "Species americanae and australienses" including 22 sections from the New World (Americas and Australia) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the low dispersal ability of the species, but despite the putative contribution of genetic drift, isolation by distance revealed that geographical distance appears to be a major component of the genetic differentiation among populations. The French population appears less distant from the North Iberian populations, as suggested by Rodriguez-Gacio et al (2009) with RAPD analyses. This relative genetic proximity is probably the result of a common biogeographical history.…”
Section: Strong Structure Between Geographic Groupsmentioning
confidence: 72%
“…1). Nevertheless, recent molecular data on this population has shown that the genetic distance between the Atlantic subpopulations (Galicia and Brittany) is lower than the distance between the Spanish subpopulations (Galicia and Castile-León) (Rodríguez-Gacio et al 2009). Moreover, the monitoring of the northwest Iberian subpopulations has revealed morphological differences between them.…”
Section: Introductionmentioning
confidence: 67%